Redesigning Independent Community Empowerment Model For Household Craftsmen - Agus Utomo; Anwar Hamdani; Riyanto Riyanto; I Gusti Putu Diva Awatara (Universitas Sebelas Maret, 2016)
Redesigning the model of independent community empowerment program can be performed by (1) reviewing the factors to develop independent empowerment for household craftsmen in Surakarta, (2) identifying various government policy that support the development of household craftsmen’s independency in Surakarta, and (3) formulate the redesigned model of independent community empowerment for household craftsmen in Surakarta. The subject of this study is household craftsmen in Surakarta, Central Java Province. This study is a research and development type, started with survey and need assessment for developing craftsmen’s independency in entrepreneurship based on community’s characters and values, media to implement the proposed model, action, and evaluation. This study will be conducted in Banjarsari sub-district in Surakarta municipality. Observation, interview, demonstration, and simulation will be employed in this study to collect the data. The data will be analyzed using mixed technique between descriptive and quantitative technique. Through FGD we will formulate the concept of redesigned model for developing independent community empowerment for household craftsmen. In this study we have collected the data on the potency of studied area; the data on the problems and supporting factors for the implementation of household craftsmen’s independency development program, (2) the data on the number of prevalent entrepreneurs, (3) performing need assessment of household craftsmen in Surakarta, which will enable us to formulate the redesigned model of independent community empowerment for household craftsmen. The final aim of this study is applying the redesigned model of independent community empowerment for household craftsmen in order to achieve entrepreneurs’ business independency.